Enhancing Financial Inclusion for Poverty Eradication: Which way for Tanzania? - Kilindo, A. A. L. (Tanzania Journal for Population studies and Development, 2009)
Development of effective financial sector policies in relation to promoting poverty-reducing economic growth has been receiving increasing global focus, and the challenges are becoming more daunting. The form of financial sector development and the institutional characteristics of the banking sector matter a lot in supporting financial stability and security, and pro-poor patterns of growth. Financial inclusion is aimed at providing banking financial services to more people in a fair transparent and equitable manner, and at affordable cost. This paper assesses the extent of financial inclusion in Tanzania. It finds out that all financial exclusion elements prevail. In reality, large numbers of the population in urban and rural areas are not accessing banking facilities and financial exclusion is common. The study recommends that poverty reduction requires the strengthening of the financial sector in terms of efficiency and regulation, boosting domestic savings, enhancing the access to credit and provision of financial services to small and medium enterprise so as to meet needs of the poor both in the urban and rural areas.